Comparative Analysis of The Family Law Systems in Indonesia and Saudi Arabia in The Context of Unregistered Marriage: Maqashid Al-Syari’ah Perspective - Nawir, Ahmad; Suarning, Suarning; Aris, Aris; L, Sudirman; Haq, Islamul (Universitas Muhammadiyah Palu, 2024)
This research analyzes family law systems in Indonesia and Saudi Arabia regarding marriage from a Maqasid al-Sharia perspective. It examines issues such as serial marriage practice, implications in both countries, and Maqashid al-Shari'ah's view on marriage registration. The study aims to analyze serial marriage practice, its implications, and Maqashid al-Shari'ah's perspective on marriage registration. It employs a library research method with a normative juridical approach. Primary sources include Islamic marriage regulations, Legal Regulations on Marriage KHI, Saudi law, and library literature. Findings reveal reasons for serial marriages in Indonesia and Saudi Arabia, influenced by social, cultural, and economic factors. Both countries face legal and social challenges for children from such marriages. Implications of serial marriages include legal uncertainty, limited access to public services, and health risks. In Indonesia, marriage status is not officially recognized, while in Saudi Arabia, women lack legal protection against health and domestic violence risks. Maqashid al-Shari'ah emphasizes maintaining religion, offspring, and property through marriage registration